PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA - Ricki Yuliardi; Ahmad Fajri Lutfi (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
This research produces a product of interactive math-based learning media flash CS6 to improve students' reasoning in learning mathematics. Methods used are Research and Development with (1) self evaluation, (2) prototyping (expert review, one-to-one, and small group), and (3) field test. Based on research results, then it can be concluded that the developed learning media already valid and effective in improving students' mathematical reasoning abilities. Based on field tests, there are significant differences in the average students before and after using flash, in other words learning media based adobe Flash effectively improve students' reasoning abilities in the concept of geometry.Keywords: Â Reasearch & Development Adobe Flash Penalaran MatematisÂ